Impact of individualized tidal volume strategies on intraoperative lung protection and inflammatory markers in laparoscopic cholecystectomy: a randomized controlled trial - Wang, Xin; Hao, Wei; Wu, Li-Fang (Frontiers in Physiology, 2025)
ObjectiveThe aim of this study is to evaluate the impact of individualized tidal volume settings, as compared to conventional settings on lung injury in patients undergoing laparoscopic cholecystectomy under mechanical ventilation.MethodsA total of 40 patients scheduled for elective laparoscopic cholecystectomy at the Affiliated Hospital of Inner Mongolia Medical University between August 2024 and January 2025 were enrolled in this randomized study. Participants were randomly assigned using a random number table to either the control group (Group C, n = 20) or the experimental group (Group T, n = 20), based on the method of tidal volume adjustment. Group C received a conventional tidal volume of 8 mL/kg. In Group T, resting tidal volume was measured preoperatively and used to individualize the mechanical ventilation settings. Serum levels of HTI56, surfactant protein A (SP-A), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) were measured at T1 (prior to anesthesia) and T4 (6 h postoperatively). Mean arterial pressure (MAP) and heart rate were recorded at four time points: T1 (baseline), T2 (20 min post-intubation), T3 (40 min post-intubation), and T4 (6 h postoperatively). Airway parameters including peak airway pressure (Ppeak), plateau pressure (Pplat), and mean airway pressure (Pmean) were documented at T2 and T3.ResultsThe average delivered tidal volume in Group T was lower than that in Group C (6.2 ± 0.5 mL/kg vs. 8.0 ± 0.3 mL/kg), indicating a statistically significant difference (p < 0.05). At T4, serum levels of IL-6, TNF-α, HTI56, and SP-A were elevated in both groups compared to preoperative values. However, the increases in these inflammatory markers were significantly greater in Group C than in Group T (p < 0.05). However, there were no significant differences between the two groups in respiratory mechanics parameters, including Ppeak, Pplat, and Pmean (p > 0.05).ConclusionIndividualized tidal volume settings were associated with significantly lower postoperative elevations of IL-6, TNF-α, HTI56, and SP-A compared to conventional settings. These findings suggest that tailoring tidal volume based on resting respiratory parameters may help mitigate lung capillary barrier injury by attenuating the inflammatory response, thereby enhancing pulmonary protection during mechanical ventilation.